Synthesis and Antimicrobial Activity of some Novel Isoindoline-1,3-Dione Derivatives - Lamie, Phoebe F. (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
New phthalimido derivatives incorporated with chalcone, pyrazole,Â  pyrazoline, and pyrimidine moieties were synthesized and evaluated for their antimicrobial activities against bacterial and fungal strains. 2-{4-[1-Acetyl-5-(4-chlorophenyl)-4,5-dihydro-1H-pyrazol-3-yl]phenyl} isoindoline-1,3-dione (7) showed broad spectrum antibacterial activity against both G+ and G- bacteria. While, (E)-2-{4-[3-(4-chlorophenyl)acryloyl]phenyl}isoindoline-1,3-dione (4b) showed promising antifungal activity.